Water retention and wood density of deadwood varies with decay classes across tree species in Austrian forests - Mathias Neumann; Sebastián Echeverría-Progulakis; Thomas Gschwantner; Tomáš Přívětivý (Forest Ecology and Management, 2026)

Development and analysis of a SmPC-based machine-readable dataset of contraindications for clinical decision support and real-world data analysis - Miriam Schechner; Wahram Andrikyan; Thomas Bauerdick; Theresa Terstegen; Louisa Redeker; Martin Federbusch; Katrin Farker; Alexander Strübing; Florian Schmidt; Petra Thürmann; Sven Schmiedl; Hanna M. Seidling; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Unrecognized contraindications pose risks for adverse drug reactions, hospitalizations or death. Clinical decision support systems (CDSS) aim to mitigate medication-related harm, particularly originating from contraindications. However, many CDSS provide limited benefit, as they focus largely on singular risk situations such as drug-drug interactions and often generate alerts of limited clinical relevance. Comprehensive integration of contraindications into CDSS may support more clinically meaningful alerts. The aim of this work was the development and analysis of machine-readable contraindication lists, including drug-clinical condition, drug-kidney function and drug-drug (group) contraindications, for integration into CDSS and real-world data analysis. Methods We extracted and operationalized contraindications, based on Summaries of Product Characteristics (SmPCs), of the 688 most prescribed drugs in Germany, leveraging common medical coding systems. Moreover, we analyzed extracted contraindications based on operationalizability, overall frequency and frequencies within different contraindication categories. Results In total, we extracted 4676 contraindications, of which 2129 (45.5%) were deemed operationalizable. Of these 2129 contraindications, 1652 (77.6%) were attributed to drug-clinical condition, 83 (3.9%) to drug-kidney, 140 (6.6%) to drug-drug group and 254 (11.9%) to drug-drug. The most frequently mentioned contraindicated risk situations were ‘severe liver insufficiency’ ( n = 74, 3.5%), ‘pregnancy’ ( n = 66, 3.1%), ‘MAO-inhibitors’ ( n = 44, 2.1%), and ‘shock’ ( n = 44, 2.1%). Conclusion Our results show, that drug-clinical condition contraindications are listed far more frequently in SmPCs than other contraindication categories. Focusing on clinical condition-related contraindications within CDSS could improve the detection of clinically relevant contraindications in routine data and enhance medication safety. The clinical applicability is currently being evaluated in the INTERPOLAR study.

Not one shoe fits all: Applicability of hydrodynamic models for the simulation of ocean alkalinity enhancement in the Baltic Sea - Anna-Adriana Anschütz; Thomas Neumann; Peter Holtermann; Hagen Radtke (Journal of Marine Systems, 2026)

A multi-class deep learning segmentation approach for automated analysis of axial and lateral roots in barley plants - Narendra Narisetti; Kerstin Neumann; Thomas Altmann; Frieder Stolzenburg; Nicolaus von Wirén; Ricardo Fabiano Giehl; Evgeny Gladilin (Computers and Electronics in Agriculture, 2026)

Fluoride distribution in volcanic rocks of the Aluto volcano complex, Main Ethiopian Rift - Lioba Virchow; Franziska Wilke; Gezahegn Yirgu; Thomas Neumann; Simona Regenspurg (Journal of African Earth Sciences, 2026)

Towards urban climate justice: Integrating social vulnerability in climate adaptation planning - Saskia Neumann; Julie M.L. Berta; Thomas Elliot; Lars Bodum (Environmental Development, 2026)

Predicting historical oxygen deficiency areas in the western Baltic Sea: A multi-model approach - Sarah Piehl; Jacob Carstensen; Thomas Neumann; Clarissa Vock (Marine Pollution Bulletin, 2025)

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

The chemistry and mineralogy of the LX high-fidelity lunar regolith simulants - Joel Patzwald; Ferry Schiperski; Hannah Fisher; Thomas Neumann; Enrico Stoll (Planetary and Space Science, 2025)

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

Characterization of river plume dynamics for a better water quality management - René Friedland; Thomas Neumann; Sarah Piehl; Hagen Radtke; Gerald Schernewski (Frontiers in Marine Science, 2025)
Excessive riverine nutrient inputs are a main driver of eutrophication in marine waters. Thus, identifying areas most affected by river plumes is a key challenge for effective water quality management. Transitional waters, which are affected by river plumes, but also have open sea characteristics, are usually merged with larger open sea assessment units. This leads to non-representative spatial units, whose unreliable assessment results cannot support the implementation of measures in order to improve the water quality. An example for this mismatch is the Oder (Odra) river plume area in the southern Baltic Sea. Due to the missing separation of the river plume area from the open sea waters, its management is suffering from the too coarse classification. We apply two model-based techniques to study the spatial and temporal variability of the Oder river plume and to follow the distribution of its nutrients and pollutants in the sea. Based on the results, we propose an improved layout for the assessment unit that better captures the spatial heterogeneity. By applying a one-way ANOVA, we show that the best size and shape of the river plume assessment unit depend on the water quality indicator being used. A smaller assessment unit near the river mouth is best for dissolved nutrients, while an area nearly four times larger is better, if chlorophyll-a is assessed. Furthermore, thresholds defining the Good Environmental Status (GES) are derived for the new unit and the remaining offshore area. These thresholds align with natural gradients and are consistent with existing GES targets already adopted by the member states of the Baltic Marine Environment Protection Commission.

Applying the science impact framework to understand real-world applications and impacts of ICESat and ICESat-2 data on decision-making - Siobhan L. Light; Molly E. Brown; Aimee R. Neeley; Thomas A. Neumann (Remote Sensing Applications: Society and Environment, 2025)

Prescribed burning as a potential regeneration technique for reed stands: a pilot study in the reed belt of Lake Neusiedl, Austria - Raffael Berner; Mathias Neumann; Mortimer Müller; Markus Hollaus; Andreas Maier; Thomas Zechmeister; Stephan Glatzel (Wetlands Ecology and Management, 2025)
Nature conservation calls for the management of reed in large stands to support the rejuvenation of reed. Traditional reed management tools at Lake Neusiedl are becoming decreasingly suitable due to insufficient freezing in winter. Therefore, prescribed burning of old Phragmites australis stands is currently being considered as a regeneration measure to promote reed regrowth and maintain invaluable habitats for specialized species in the reed belt. In January 2024 a pilot study was carried out near the municipality of Jois to gain insights into suitability and consequences of controlled burning of old reed mats in the reed belt. Applied methods include pre- and post-fire biomass and carbon content analyses from vegetation, litter and soil, fire behavior and intensity monitoring, moisture content measurements during and after the fire, and area-wide UAV-LiDAR mapping. Mean fire temperature was approx. 700 °C and peaked at 1034 °C. 15.57 ha of the 32 ha study area were affected by the fire, and a total of 57.84 tons of carbon were released (3.72 t C/ha). On burnt areas standing vegetation was removed and litter thickness significantly reduced by approx. 30%, while no biomass loss from soil was detected. Fuel moisture content is negatively correlated to distance from the water table and has mitigating effects on fire spread if above 30%, resulting in unaffected deeper layers and numerous unburnt refugia patches within the fire perimeter. Our results indicate that prescribed fire can be a suitable management tool at Lake Neusiedl for the purpose of reed rejuvenation and wetland habitat regeneration.

Genome-wide association study of Fuchs’ endothelial corneal dystrophy in the German population - Juliane Fechner; Guilherme B. Neumann; Fabia Murza; Leonard Matthias; Marcus Walckling; Claudia Brockmann; Thomas A. Fuchsluger; Tobias Brockmann (Human Genetics, 2025)
The genetic etiology of Fuchs Endothelial Corneal Dystrophy (FECD) is not yet fully elucidated. While the disease is widespread and the leading indication for corneal transplantation in the Western world, the concurrent shortage of corneal transplants underscores the urgent need for further research into the underlying mechanisms. Such investigations could enable the development of innovative therapeutic strategies. Therefore, we aimed to verify candidate genes previously identified and sought after novel variants in the German population. Undertaking a genome wide association study (GWAS) using the Axiom™ Precision Medicine Diversity Array on 157 FECD cases and 309 controls, followed by pathway enrichment analysis, we were able to confirm the significance of the TCF4 locus (rs613872, p = 8.0 × 10 − 23 , OR = 8.60, h 2 = 0.72) and identified a range of novel variants. Further fine-mapping highlighted novel candidate SNPs, such as on chromosome 5 in the SEMA6A gene (rs153643, p = 3.1 × 10 − 9 , OR = 2.75, h 2 = 0.30), and on chromosome 19 in the DNAJC19P3 gene (rs62117964, p = 3.3 × 10 − 8 , OR = 3.61, h 2 = 0.29). SEMA6A gene is involved in apoptotic pathways and cytoskeletal remodeling, making it an interesting candidate gene for further investigations as a potential therapeutic target. Furthermore, several variants were identified in lncRNAs, which presumably influence the expression of nearby protein-coding genes. For example, LOC105372130 , which is associated with corneal hysteresis and corneal resistance factor, may influence the expression of TCF4 .

Robust algorithm for automatic surface-based outlier detection in MBES point clouds - Bahareh Mohammadivojdan; Felix Lorenz; Thomas Artz; Robert Weiß; Frederic Hake; Yazan Alkhatib; Ingo Neumann; Hamza Alkhatib (Marine Geodesy, 2025)

Warm saltwater inflows strengthen oxygen depletion in the western Baltic Sea - Leonie Barghorn; H. E. Markus Meier; Hagen Radtke; Thomas Neumann; Lev Naumov (Climate Dynamics, 2025)
Hypoxia is a major environmental threat for coastal seas, including the strongly-stratified Baltic Sea in northern Europe. There, a pronounced increase in nutrient loads since the 1950s led to the development of one of the largest hypoxic areas worldwide. So far, other drives of hypoxia, like the increase in water temperatures due to global warming, have been considered minor compared to eutrophication. We show, by analyzing 159-years long hindcast simulations of three different Baltic Sea models, that exceptional warming trends in deep water layers of the western Baltic Sea deteriorated the local oxygen conditions. The above-average warming is only to a small extent attributed directly to global warming, but mainly to a shift in the seasonality of saltwater inflows from the North Sea towards more warm summer and early autumn inflows. Hence, we identify a so far unknown driver of oxygen depletion in the western Baltic Sea with potentially serious ecological consequences.

Trace element partitioning between natural barite and deep anoxic groundwaters: Implications for radionuclide retention in host rocks of nuclear waste repositories - Ferdinand Kirchner; Martin Kutzschbach; Henrik Drake; Vanessa Fichtner; Piotr M. Kowalski; Stefan Rudin; Martin J. Whitehouse; Mikael Tillberg; Thomas Neumann (Applied Geochemistry, 2024)

Climate variability in a 3.8 Ma old sedimentary record from the hyperarid Atacama Desert - Felix L. Arens; Jenny Feige; Alessandro Airo; Christof Sager; Lutz Hecht; Lucas Horstmann; Felix E.D. Kaufmann; Johannes Lachner; Thomas Neumann; Norbert Nowaczyk; Ferry Schiperski; Peter Steier; et al. (Global and Planetary Change, 2024)

TGFβ signalling pathway impacts brain metastases profiles in locally advanced colorectal cancer - Sven Jacob; Ilja Balonov; Vindi Jurinovic; Christian Heiliger; Tengis Tschaidse; Jörg Kumbrink; Thomas Kirchner; Jens Werner; Martin K. Angele; Marlies Michl; Jens Neumann (Clinical & Experimental Metastasis, 2024)
Rationale Colorectal Cancer (CRC) represents the third most common type of cancer in Germany and the second most common cancer-related cause of death worldwide. Distant metastases are still the main limit for patient survival. While liver metastases as well as peritoneal carcinomatosis can often either be resected or treated with systemic therapy, little options remain for brain metastases. Additionally, a number of studies has already investigated hepatic, peritoneal, pulmonary as well as continuing distant metastases in colorectal cancer. Yet, with respect to tumor biology and brain metastases, little is known so far. Material and methods Two cohorts, M0 without distant spread and BRA with brain metastases were build. RNA was isolated from paraffin embedded specimen. Gene expression was performed by an RNA NanoString-Analysis using the nCounter® PanCancer Progression Panel by NanoString-Technologies (Hamburg, Germany). Results were analysed by principal component analysis, gene expression and pathway analysis using commonly available databases such as KEGG as benchmark for comparison. Results We were able to determine a gene signature that provides a sophisticated group separation between M0 and BRA using principal component analysis. All genes with strong loading characteristics on principal component 1 were cross-referenced with the subsequently performed accurate gene set enrichment analysis (GSEA). The GSEA revealed a clear dysregulation of the TGFβ pathway in compared cohorts M0 and BRA. Interestingly, the targeted pathways analysis of the identified genes confirmed that in fact almost all strong loading genes of PC1 play a role in the TGFβ pathway. Conclusion Our results suggest the TGFβ pathway as a crucial player in the development of brain metastases in primary CRC. In some types of colorectal cancer, downregulation of the TGFβ pathway might hinder primary colorectal cancer to metastasize to the nervous system. While the paradoxical functioning of the TGFβ pathway is still not fully understood, these shed light on yet another clinical implication of this complex pathway.

Club cell protein (CC16) in serum as an effect marker for small airway epithelial damage caused by diesel exhaust and blasting fumes in potash mining - Savo Neumann; Swaantje Casjens; Frank Hoffmeyer; Katrin Rühle; Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Jörg Giesen; Volker Neumann; Dirk Taeger; Dirk Pallapies; Thomas Birk; et al. (International Archives of Occupational and Environmental Health, 2024)
Objective The effect marker club cell protein (CC16) is secreted by the epithelium of the small respiratory tract into its lumen and passes into the blood. Increased amounts of CC16 in serum are observed during acute epithelial lung injury due to air pollutants. CC16 in serum was determined as part of this cross-sectional study in underground potash miners on acute and chronic health effects from exposures to diesel exhaust and blasting fumes. Methods Nitrogen oxides, carbon monoxide, and diesel particulate matter were measured in 672 workers at a German potash mining site on a person-by-person basis over an early shift or midday shift, together with CC16 serum concentrations before and after the respective shift. CC16 concentrations and CC16 shift-differences were evaluated with respect to personal exposure measurements and other quantitative variables by Spearman rank correlation coefficients. CC16 shift-differences were modeled using multiple linear regression. Above-ground workers as reference group were compared to the exposed underground workers. Results Serum concentrations of CC16 were influenced by personal characteristics such as age, smoking status, and renal function. Moreover, they showed a circadian rhythm. While no statistically significant effects of work-related exposure on CC16 concentrations were seen in never smokers, such effects were evident in current smokers. Conclusion The small airways of current smokers appeared to be vulnerable to the combination of measured work-related exposures and individual exposure to smoking. Therefore, as health protection of smokers exposed to diesel exhaust and blasting fumes, smoking cessation is strongly recommended.

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

Assessment of climate extremes at the regional scale during the last millennium using an annually resolved stalagmite record - Tobias Kluge; Philipp Holz; Thomas Neumann; Elisabeth Eiche; Maximilian Schuh; Norbert Frank; Ronny Friedrich; Alexander Land; Mario Trieloff; Axel K. Schmitt (Earth and Planetary Science Letters, 2023)

Dynamics of oxygen sources and sinks in the Baltic Sea under different nutrient inputs - Lev Naumov; H. E. Markus Meier; Thomas Neumann (Frontiers in Marine Science, 2023)
The Baltic Sea is one of the marine systems suffering from pronounced man-made hypoxia due to the elevated nutrient loads from land. To mitigate hypoxia expansion and to return the Baltic Sea to a good environmental state, the Baltic Sea Action Plan (BSAP), regulating the waterborne and airborne nutrient input, was adopted by all states surrounding the Baltic Sea. However, at the moment, no significant shrinking of the hypoxic area is observed. In this study, two scenario simulations of the future state of the deep parts of the central Baltic Sea (deeper than 70 meters) were carried out, utilizing a 3-dimensional numerical model. Climate change effects on meteorology, hydrology, and oceanic state were not included. We focused on O 2 and H 2 S sources and sinks under different nutrient input scenarios. We found that under the BSAP scenario, all subbasins in the central Baltic Sea, especially the northern and western Gotland Basin, show significant improvement, namely, oxygenation and oxidation of the deposited reduced material, ceasing its advection to the upper layers and neighboring basins. We found that the nutrient loads are responsible for more than 60% and 80% of the O 2 and H 2 S sources and sinks variability, respectively, at the interannual time scale. We showed that the Baltic Sea could return to the initial state in 1948, but under the more rigorous 0.5 BSAP scenario (nutrient input is halved compared to the BSAP). However, since we observed no hysteresis effect, the system would probably reach the initial state but over a timeframe longer than the 71-year future simulation period.

Deoxygenation of the Baltic Sea during the last millennium - Florian Börgel; Thomas Neumann; Jurjen Rooze; Hagen Radtke; Leonie Barghorn; H. E. Markus Meier (Frontiers in Marine Science, 2023)
Over the last 1,000 years, changing climate strongly influenced the ecosystem of coastal oceans such as the Baltic Sea. Sedimentary records revealed that changing temperatures could be linked to changing oxygen levels, spreading anoxic, oxygen-free areas in the Baltic Sea. However, the attribution of changing oxygen levels remains to be challenging. This work simulates a preindustrial period of 850 years, covering the Medieval Climate Anomaly (MCA) and the Little Ice Age using a coupled physical-biogeochemical model. We conduct a set of sensitivity studies that allow us to disentangle the contributions of different biogeochemical processes to increasing hypoxia during the last millennium. We find that the temperature-dependent mineralization rate is a key process contributing to hypoxia formation during the MCA. Faster mineralization enhances the vertical phosphorus flux leading to higher primary production. Our results question the hypothesis that increased cyanobacteria blooms are the reason for increased hypoxia in the Baltic Sea during the MCA. Moreover, the strong contribution of the mineralization rate suggests that the role of temperature-dependent mineralization in current projections should be revisited.

Impact of diesel exhaust exposure on urinary 1-hydroxypyrene in underground salt and potash workers - Swaantje Casjens; Savo Neumann; Katrin Rühle; Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Thomas Birk; Jörg Giesen; Volker Neumann; Dirk Pallapies; Jürgen Bünger; Heiko U. Käfferlein; et al. (International Journal of Hygiene and Environmental Health, 2023)

Modeling of Water Quality Indicators in the Western Baltic Sea: Seasonal Oxygen Deficiency - Sarah Piehl; René Friedland; Birgit Heyden; Wera Leujak; Thomas Neumann; Gerald Schernewski (Environmental Modeling & Assessment, 2023)
Hypoxia in coastal seas is a severe threat to marine ecosystems, with the Baltic Sea exhibiting the largest hypoxic areas worldwide. While perennial oxygen deficiency in the deep basins is a component of environmental assessments, seasonal oxygen deficiency in shallow areas is not routinely assessed. Current measurements alone cannot provide the spatio-temporal resolution needed for highly dynamic seasonal oxygen deficiency, making estimations on its duration and extent uncertain. Utilizing long-term 3D model simulations with a horizontal resolution of 3 nautical miles, we analyzed the development of seasonal oxygen deficiency in the western Baltic Sea. Different metrics (near-bottom area, water volume, duration, and frequency) and critical oxygen concentrations were analyzed for exemplary sub-basins as defined by the Helsinki Commission. Our results indicate that the extent of seasonal oxygen deficiency has continually increased in the second half of the twentieth century until the end of the 1980s and slightly decreased in the last two decades. In the 1950s, the spatial extent of oxygen deficiency was still at a low plateau before increasing, indicating that this period could be suitable as a reference period representing a good status, including naturally occurring oxygen deficiency. Overall, seasonal oxygen deficiency is a suitable indicator for describing the ecological status of the western Baltic Sea. For an application as eutrophication indicator in shallow areas, a sufficient spatio-temporal resolution of seasonal oxygen deficiency is needed which can be gained by a combination of model simulations and measurements. Further analysis is needed to integrate in situ measurements and model results to obtain the most reliable approach.

Limited ventilation of the central Baltic Sea due to elevated oxygen consumption - Lev Naumov; Thomas Neumann; Hagen Radtke; H. E. Markus Meier (Frontiers in Marine Science, 2023)
The Baltic Sea is known as the world’s largest marine system suffering from accelerating, man-made hypoxia. Notably, despite the nutrient load reduction policy adopted in the 1980s, the oxygen conditions of the Baltic Sea’s deep waters are still worsening. This study disentangles oxygen and hydrogen sulfide sources and sinks using the results from the 3-dimensional coupled MOM-ERGOM numerical model and investigates ventilation of the deep central Baltic Sea by the 29 biggest oxygen inflows from 1948 to 2018 utilizing the element tagging technic. Everywhere across the central Baltic Sea, except in the Bornholm Basin, a shift in oxygen consumption from sediments to water column and a significant positive trend in hydrogen sulfide content were observed. The most notable changes happened in the northern and western Gotland basins. Mineralization of organic matter, both in the water column and sediments, was identified as the primary driver of the observed changes. A significant negative trend in the lifetime of inflowing oxygen was found everywhere in the central Baltic Sea. It leads to the reduced efficiency of natural ventilation of the central Baltic Sea via the saltwater inflows, especially in the northern and western Gotland basins.

Near equatorial paleoclimatic evolution and control on organic matter accumulation during the Cenomanian in the Abu Gharadig Basin, southern Tethys: Insights from palynology, organic petrography, and geochemistry - Ahmed Mansour; Thomas Gentzis; Sameh S. Tahoun; Mohamed S. Ahmed; Susanne Gier; Humberto Carvajal-Ortiz; Jacob Neumann; Xiugen Fu; Jian Wang (International Journal of Coal Geology, 2023)

Paleoenvironmental, paleoclimatic, and organic matter assessment of the hybrid Kharita Formation (Albian) in the Abu Gharadig Basin, Egypt: Integration between palynology, organic petrography, and organic geochemistry - Ahmed Mansour; Thomas Gentzis; Sameh S. Tahoun; Mohamed S. Ahmed; Michael Wagreich; Humberto Carvajal-Ortiz; Jacob Neumann; Ahmed E. Radwan (Marine and Petroleum Geology, 2023)

Al-Mg and U-Pb chronological records of Erg Chech 002 ungrouped achondrite meteorite - Philip M. Reger; Yvonne Roebbert; Wladimir Neumann; Abdelmouhcine Gannoun; Marcel Regelous; Winfried H. Schwarz; Thomas Ludwig; Mario Trieloff; Stefan Weyer; Audrey Bouvier (Geochimica et Cosmochimica Acta, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Underground salt and potash workers exposed to nitrogen oxides and diesel exhaust: assessment of specific effect biomarkers - Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Katrin Rühle; Annette M. Bachand; Lori Crawford; Kenneth A. Mundt; Jürgen Bünger; Dirk Pallapies; Dirk Taeger; Swaantje Casjens; Anja Molkenthin; et al. (International Archives of Occupational and Environmental Health, 2022)
Purpose Occupational exposure limits (OEL) for nitrogen oxides (NO, NO 2 ) and diesel exhaust (EC-DPM) were reassessed by the German authorities in 2016/2017. We performed a clinical cross-sectional study among salt and potash underground workers exposed to these substances at relatively high levels to examine possible indicators of acute effects on workers’ health. Methods We measured post- versus pre-shift differences in cardiovascular, inflammatory, immune, and respiratory effect biomarkers and assessed their associations with personal exposures measured during the same shift. We also compared post- versus pre-shift differences in biomarker levels between exposure groups defined based on work site and job type. Results None of the above-ground workers exceeded the OEL for NO 2 and only 5% exceeded the OEL for EC-DPM exposure. Among underground workers, 33% of miners and 7% underground maintenance workers exceeded the OEL for NO 2 ; the OEL for EC-DPM was exceeded by 56% of miners and 17% of maintenance workers. Some effect biomarkers (thrombocytes, neutrophils, MPO, TNF-α, IgE, FeNO) showed statistically significant differences between pre- versus post-shift measurements; however, there were no consistent associations between pre- and post-shift differences and exposure group or personal exposure measurements during the shift. Conclusions We did not find evidence of associations between workplace exposure to NO, NO 2 or EC-DPM and clinically relevant indicators of acute cardiovascular, inflammatory and immune, or respiratory effects among salt and potash underground workers in Germany.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)

Effects of Nutrient Management Scenarios on Marine Eutrophication Indicators: A Pan-European, Multi-Model Assessment in Support of the Marine Strategy Framework Directive - René Friedland; Diego Macias; Gianpiero Cossarini; Ute Daewel; Claude Estournel; Elisa Garcia-Gorriz; Bruna Grizzetti; Marilaure Grégoire; Bo Gustafson; Sofia Kalaroni; Onur Kerimoglu; Paolo Lazzari; et al. (Frontiers in Marine Science, 2021)
A novel pan-European marine model ensemble was established, covering nearly all seas under the regulation of the Marine Strategy Framework Directive (MSFD), with the aim of providing a consistent assessment of the potential impacts of riverine nutrient reduction scenarios on marine eutrophication indicators. For each sea region, up to five coupled biogeochemical models from institutes all over Europe were brought together for the first time. All model systems followed a harmonised scenario approach and ran two simulations, which varied only in the riverine nutrient inputs. The load reductions were evaluated with the catchment model GREEN and represented the impacts due to improved management of agriculture and wastewater treatment in all European river systems. The model ensemble, comprising 15 members, was used to assess changes to the core eutrophication indicators as defined within MSFD Descriptor 5. In nearly all marine regions, riverine load reductions led to reduced nutrient concentrations in the marine environment. However, regionally the nutrient input reductions led to an increase in the non-limiting nutrient in the water, especially in the case of phosphate concentrations in the Black Sea. Further core eutrophication indicators, such as chlorophyll-a, bottom oxygen and the Trophic Index TRIX, improved nearly everywhere, but the changes were less pronounced than for the inorganic nutrients. The model ensemble displayed strong consistency and robustness, as most if not all models indicated improvements in the same areas. There were substantial differences between the individual seas in the speed of response to the reduced nutrient loads. In the North Sea ensemble, a stable plateau was reached after only three years, while the simulation period of eight years was too short to obtain steady model results in the Baltic Sea. The ensemble exercise confirmed the importance of improved management of agriculture and wastewater treatments in the river catchments to reduce marine eutrophication. Several shortcomings were identified, the outcome of different approaches to compute the mean change was estimated and potential improvements are discussed to enhance policy support. Applying a model ensemble enabled us to obtain highly robust and consistent model results, substantially decreasing uncertainties in the scenario outcome.

Auswirkungen des Klimawandels auf das Grundwasser und die Wasserversorgung in Süddeutschland - Ronja Fliß; Christof Baumeister; Thomas Gudera; Mario Hergesell; Benjamin Kopp; Jörg Neumann; Miriam Posselt (Grundwasser, 2021)
Zusammenfassung Für die öffentliche Trinkwasserversorgung in Süddeutschland wird größtenteils Grund- und Quellwasser genutzt. Der Kenntnis über die Entwicklung des Bodenwasserhaushalts und insbesondere der Grundwasserneubildung kommt somit eine große Bedeutung zu. Im Rahmen der Kooperation KLIWA (Klimaveränderung und Konsequenzen für die Wasserwirtschaft, www.kliwa.de ) wurde die Entwicklung des Bodenwasserhaushaltes und der Grundwasserneubildung aus Niederschlag für den Zeitraum von 1951 bis 2019 für die Länder Baden-Württemberg, Bayern, Hessen und Rheinland-Pfalz mit dem Bodenwasserhaushaltmodell GWN-BW modelliert. Seit Ende der 1980er-Jahre zeigt sich ein Anstieg der mittleren jährlichen Temperatur in Süddeutschland. Die jährlichen Niederschlagssummen haben sich in der jüngeren Vergangenheit (seit 2003) reduziert und somit eine deutliche Verringerung der Grundwasserneubildung aus Niederschlag bewirkt. Gleichzeitig ist eine Zunahme des Trockenheitsindex (Anzahl an Tagen mit Füllung des Bodenwasserspeichers < 30 % der nutzbaren Feldkapazität) zu erkennen. Häufiger werdende und länger anhaltende Trockenperioden stellen auch die Wasserwirtschaft zunehmend vor Herausforderungen und bedürfen der frühzeitigen Entwicklung von Handlungsoptionen, z. B. auf der Basis des hier vorgestellten „Trockenwetterdargebots“, um Nutzungskonflikte zu entschärfen.

Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)
Background Frailty and adverse drug effects are linked in the fact that polypharmacy is correlated with the severity of frailty; however, a causal relation has not been proven in older people with clinically manifest frailty. Methods A literature search was performed in Medline to detect prospective randomized controlled trials (RCTs) testing the effects of pharmacological interventions or medication optimization in older frail adults on comprehensive frailty scores or partial aspects of frailty that were published from January 1998 to October 2019. Results Twenty-five studies were identified, 4 on comprehensive frailty scores and 21 on aspects of frailty. Two trials on comprehensive frailty scores showed positive results on frailty although the contribution of medication review in a multidimensional approach was unclear. In the studies on aspects related to frailty, ten individual drug interventions showed improvement in physical performance, muscle strength or body composition utilizing alfacalcidol, teriparatide, piroxicam, testosterone, recombinant human chorionic gonadotropin, or capromorelin. There were no studies examining negative effects of drugs on frailty. Conclusion So far, data on a causal relationship between drugs and frailty are inconclusive or related to single-drug interventions on partial aspects of frailty. There is a clear need for RCTs on this topic that should be based on a comprehensive, internationally consistent and thus reproducible concept of frailty assessment.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Ventilation of the northern Baltic Sea - Thomas Neumann; Herbert Siegel; Matthias Moros; Monika Gerth; Madline Kniebusch; Daniel Heydebreck (Ocean Science, 2020)
The Baltic Sea is a semi-enclosed, brackish water sea in northern Europe. The deep basins of the central Baltic Sea regularly show hypoxic conditions. In contrast, the northern parts of the Baltic Sea, the Bothnian Sea and Bothnian Bay, are well oxygenated. Lateral inflows or a ventilation due to convection are possible mechanisms for high oxygen concentrations in the deep water of the northern Baltic Sea. In March 2017, conductivity–temperature–depth (CTD) profiles and bottle samples, ice core samples, and brine were collected in the Bothnian Bay. In addition to hydrographic standard parameters, light absorption has been measured in all samples. A complementary numerical model simulation provides quantitative estimates of the spread of newly formed bottom water. The model uses passive and age tracers to identify and trace different water masses. Observations indicate a recent ventilation of the deep bottom water at one of the observed stations. The analysis of observations and model simulations shows that the Bothnian Bay is ventilated by dense water formed due to mixing of Bothnian Sea and Bothnian Bay surface water initializing lateral inflows. The observations show the beginning of the inflow and the model simulation demonstrates the further northward spreading of bottom water. These events occur during wintertime when the water temperature is low. Brine rejected during ice formation barely contributes to dense bottom water.

Cellular organization and histogenesis of adenosquamous carcinoma of the pancreas: evidence supporting the squamous metaplasia concept - Werner Boecker; Katharina Tiemann; Joerg Boecker; Marieta Toma; Michael H. Muders; Thomas Löning; Igor Buchwalow; Karl J. Oldhafer; Ulf Neumann; Bernd Feyerabend; Andre Fehr; Göran Stenman (Histochemistry and Cell Biology, 2020)
Adenosquamous carcinoma of the pancreas (ASCAP) is characterized by conventional pancreatic ductal adenocarcinoma (PDAC) and squamous carcinoma components with at least 30% of the tumour showing squamous differentiation. To get further insight into the histogenesis of these lesions, we analysed the cellular organization of ASCAP compared to PDACs. Using Immunohistochemistry and triple immunofluorescence labelling studies for keratins, p63, p40, MUC1, MUC2, MUC5AC, Ki67, and EGFR we demonstrate that many ASCAPs contain a transitional zone between the K8/18-positive adenocarcinomatous component and the p63+ /p40+ /K5/K14+ squamous component initiated by the expression of p63 in K8/18+ adenocarcinomatous cells and the appearance of basally located p63+ K5/14+ cells. p63+ K5/14+ cells give rise to fully developed squamous differentiation. Notably, 25% of conventional PDACs without histologically recognizable squamous component contain foci of p63+ p40+ and K5/14+ cells similar to the transitional zone. Our data provide evidence that the squamous carcinoma components of ASCAPs originate from pre-existing PDAC via transdifferentiation of keratin K8/18-positive glandular cells to p63-, p40-, and keratin K5/14-positive squamous carcinoma cells supporting the squamous metaplasia hypothesis. Thus our findings provide new evidence about the cellular process behind squamous differentiation in ASCAPs.

Comparison of three types of laser optical disdrometers under natural rainfall conditions - Lisbeth Lolk Johannsen; Nives Zambon; Peter Strauss; Tomas Dostal; Martin Neumann; David Zumr; Thomas A. Cochrane; Günter Blöschl; Andreas Klik (Hydrological Sciences Journal, 2020)

Quantifying the contribution of shipping NO x emissions to the marine nitrogen inventory – a case study for the western Baltic Sea - Daniel Neumann; Matthias Karl; Hagen Radtke; Volker Matthias; René Friedland; Thomas Neumann (Ocean Science, 2020)
The western Baltic Sea is impacted by various anthropogenic activities and stressed by high riverine and atmospheric nutrient loads. Atmospheric deposition accounts for up to a third of the nitrogen input into the Baltic Sea and contributes to eutrophication. Amongst other emission sources, the shipping sector is a relevant contributor to the atmospheric concentrations of nitrogen oxides (NOX) in marine regions. Thus, it also contributes to atmospheric deposition of bioavailable oxidized nitrogen into the Baltic Sea. In this study, the contribution of shipping emissions to the nitrogen budget in the western Baltic Sea is evaluated with the coupled three-dimensional physical biogeochemical model MOM–ERGOM (Modular Ocean Model–Ecological ReGional Ocean Model) in order to assess the relevance of shipping emissions for eutrophication. The atmospheric input of bioavailable nitrogen impacts eutrophication differently depending on the time and place of input. The shipping sector contributes up to 5 % to the total nitrogen concentrations in the water. The impact of shipping-related nitrogen is highest in the offshore regions distant from the coast in early summer, but its contribution is considerably reduced during blooms of cyanobacteria in late summer because the cyanobacteria fix molecular nitrogen. Although absolute shipping-related total nitrogen concentrations are high in some coastal regions, the relative contribution of the shipping sector is low in the vicinity of the coast because of high riverine nutrient loads.

Living on the edge: reproduction, dispersal potential, maternal effects and local adaptation in aquatic, extremophilic invertebrates - Guntram Weithoff; Catherin Neumann; Jacqueline Seiferth; Thomas Weisse (Aquatic Sciences, 2019)

Assessment of Uncertainties in Scenario Simulations of Biogeochemical Cycles in the Baltic Sea - H. E. Markus Meier; Moa Edman; Kari Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2019)

Brain neuropeptide S: via GPCR activation to a powerful neuromodulator of socio-emotional behaviors - Thomas Grund; Inga D. Neumann (Cell and Tissue Research, 2019)

Assessment of Eutrophication Abatement Scenarios for the Baltic Sea by Multi-Model Ensemble Simulations - H. E. Markus Meier; Moa K. Edman; Kari J. Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2018)

Long-Term Mean Circulation of the Baltic Sea as Represented by Various Ocean Circulation Models - Manja Placke; H. E. Markus Meier; Ulf Gräwe; Thomas Neumann; Claudia Frauen; Ye Liu (Frontiers in Marine Science, 2018)

Climate change effects on denitrification and associated avoidance costs in three Baltic river basin - coastal sea systems - Alexander Allin; Gerald Schernewski; Rene Friedland; Thomas Neumann; Hagen Radtke (Journal of Coastal Conservation, 2017)

Tubulin alpha 8 is expressed in hepatic stellate cells and is induced in transformed hepatocytes - Lisa Rein-Fischboeck; Rebekka Pohl; Elisabeth M. Haberl; Sebastian Zimny; Maximilian Neumann; Kristina Eisinger; Thomas S. Weiss; Sabrina Krautbauer; Christa Buechler (Molecular and Cellular Biochemistry, 2017)

Mutation in S6 domain of HCN4 channel in patient with suspected Brugada syndrome modifies channel function - Stephanie Biel; Marco Aquila; Brigitte Hertel; Anne Berthold; Thomas Neumann; Dario DiFrancesco; Anna Moroni; Gerhard Thiel; Silke Kauferstein (Pflügers Archiv - European Journal of Physiology, 2016)

Crowdfunding als Chance für Unternehmens-gründungen in den Lebenswissenschaften - Thomas Neumann (BIOspektrum, 2016)

Echoes from the Past: A Healthy Baltic Sea Requires More Effort - Aarno T. Kotilainen; Laura Arppe; Slawomir Dobosz; Eystein Jansen; Karoline Kabel; Juha Karhu; Mia M. Kotilainen; Antoon Kuijpers; Bryan C. Lougheed; H. E. Markus Meier; Matthias Moros; Thomas Neumann; et al. (Ambio, 2014)

Forest floor vegetation response to nitrogen deposition in Europe - Thomas Dirnböck; Ulf Grandin; Markus Bernhardt‐Römermann; Burkhardt Beudert; Roberto Canullo; Martin Forsius; Maria‐Theresia Grabner; Maria Holmberg; Sirpa Kleemola; Lars Lundin; Michael Mirtl; Markus Neumann; et al. (Global Change Biology, 2014)
Chronic nitrogen (N) deposition is a threat to biodiversity that results from the eutrophication of ecosystems. We studied long‐term monitoring data from 28 forest sites with a total of 1,335 permanent forest floor vegetation plots from northern Fennoscandia to southern Italy to analyse temporal trends in vascular plant species cover and diversity. We found that the cover of plant species which prefer nutrient‐poor soils (oligotrophic species) decreased the more the measured N deposition exceeded the empirical critical load ( CL ) for eutrophication effects ( P = 0.002). Although species preferring nutrient‐rich sites (eutrophic species) did not experience a significantly increase in cover ( P = 0.440), in comparison to oligotrophic species they had a marginally higher proportion among new occurring species ( P = 0.091). The observed gradual replacement of oligotrophic species by eutrophic species as a response to N deposition seems to be a general pattern, as it was consistent on the European scale. Contrary to species cover changes, neither the decrease in species richness nor of homogeneity correlated with nitrogen CL exceedance (ExCL emp N). We assume that the lack of diversity changes resulted from the restricted time period of our observations. Although existing habitat‐specific empirical CL still hold some uncertainty, we exemplify that they are useful indicators for the sensitivity of forest floor vegetation to N deposition.

Darbepoetin inhibits proliferation of hepatic cancer cells in the presence of TGF-β - Sabrina Ehnert; Thomas Freude; Carmen Eicher; Britta Burkhardt; Juan J. Martínez Sánchez; Jan Neumann; Ruben Mühl-Benninghaus; Steven Dooley; Stefan Pscherer; Andreas K. Nussler (Archives of Toxicology, 2014)

Combined effects of global climate change and regional ecosystem drivers on an exploited marine food web - Susa Niiranen; Johanna Yletyinen; Maciej T. Tomczak; Thorsten Blenckner; Olle Hjerne; Brian R. MacKenzie; Bärbel Müller‐Karulis; Thomas Neumann; H. E. Markus Meier (Global Change Biology, 2013)
Changes in climate, in combination with intensive exploitation of marine resources, have caused large‐scale reorganizations in many of the world's marine ecosystems during the past decades. The B altic S ea in N orthern E urope is one of the systems most affected. In addition to being exposed to persistent eutrophication, intensive fishing, and one of the world's fastest rates of warming in the last two decades of the 20th century, accelerated climate change including atmospheric warming and changes in precipitation is projected for this region during the 21st century. Here, we used a new multimodel approach to project how the interaction of climate, nutrient loads, and cod fishing may affect the future of the open C entral B altic S ea food web. Regionally downscaled global climate scenarios were, in combination with three nutrient load scenarios, used to drive an ensemble of three regional biogeochemical models ( BGM s). An Ecopath with Ecosim food web model was then forced with the BGM results from different nutrient‐climate scenarios in combination with two different cod fishing scenarios. The results showed that regional management is likely to play a major role in determining the future of the Baltic Sea ecosystem. By the end of the 21st century, for example, the combination of intensive cod fishing and high nutrient loads projected a strongly eutrophicated and sprat‐dominated ecosystem, whereas low cod fishing in combination with low nutrient loads resulted in a cod‐dominated ecosystem with eutrophication levels close to present. Also, nonlinearities were observed in the sensitivity of different trophic groups to nutrient loads or fishing depending on the combination of the two. Finally, many climate variables and species biomasses were projected to levels unseen in the past. Hence, the risk for ecological surprises needs to be addressed, particularly when the results are discussed in the ecosystem‐based management context.

Extremes of Temperature, Oxygen and Blooms in the Baltic Sea in a Changing Climate - Thomas Neumann; Kari Eilola; Bo Gustafsson; Bärbel Müller-Karulis; Ivan Kuznetsov; H. E. Markus Meier; Oleg P. Savchuk (Ambio, 2012)

Impact of Climate Change on Ecological Quality Indicators and Biogeochemical Fluxes in the Baltic Sea: A Multi-Model Ensemble Study - H. E. Markus Meier; Bärbel Müller-Karulis; Helén C. Andersson; Christian Dieterich; Kari Eilola; Bo G. Gustafsson; Anders Höglund; Robinson Hordoir; Ivan Kuznetsov; Thomas Neumann; Zohreh Ranjbar; Oleg P. Savchuk; et al. (Ambio, 2012)

Reconstructing the Development of Baltic Sea Eutrophication 1850–2006 - Bo G. Gustafsson; Frederik Schenk; Thorsten Blenckner; Kari Eilola; H. E. Markus Meier; Bärbel Müller-Karulis; Thomas Neumann; Tuija Ruoho-Airola; Oleg P. Savchuk; Eduardo Zorita (Ambio, 2012)

Mercury exposure and neurochemical impacts in bald eagles across several Great Lakes states - Jennifer Rutkiewicz; Dong-Ha Nam; Thomas Cooley; Kay Neumann; Irene Bueno Padilla; William Route; Sean Strom; Niladri Basu (Ecotoxicology, 2011)

Strong genetic differentiation and postglacial origin of populations in the marine midge Clunio marinus (Chironomidae, Diptera) - TOBIAS S. KAISER; DIETRICH NEUMANN; DAVID G. HECKEL; THOMAS U. BERENDONK (Molecular Ecology, 2010)

Geowissenschaftliche bewertung von karsthöhlen für die wasserbewirtschaftung in gunung sewu - Thomas Neumann; Zsolt Berner; Doris Stüben; Syaeful Bahri; Makky Jaya (WASSERWIRTSCHAFT, 2009)

Holocene vegetation and climate history of the northern Golan heights (Near East) - Frank Neumann; Christian Schölzel; Thomas Litt; Andreas Hense; Mordechai Stein (Vegetation History and Archaeobotany, 2007)

Holocene vegetation and climate history of the northern Golan heights (Near East) - Frank Neumann; Christian Schölzel; Thomas Litt; Andreas Hense; Mordechai Stein (Vegetation History and Archaeobotany, 2007)

Evidence for a new contiguous gene syndrome, the chromosome 16p13.3 deletion syndrome alias severe Rubinstein–Taybi syndrome - Oliver Bartsch; Sasan Rasi; Alicia Delicado; Sarah Dyack; Luitgard M. Neumann; Eva Seemanová; Marianne Volleth; Thomas Haaf; Vera M. Kalscheuer (Human Genetics, 2006)

Land Use-related Chemical Composition of Street Sediments in Beijing - Cen Kuang; Thomas Neumann; Stefan Norra; Doris Stüben (Environmental Science and Pollution Research, 2004)

Segmentation of the southern Mariana back‐arc spreading center - Doris StÜben; Thomas Neumann; Nasr‐Eddine Taibi; GeoffreyP. Glasby (Island Arc, 1998)
SeaBeam multibeam bathymetry obtained during cruise SO‐69 of research vessel (R/V) Sonne defines the segmentation and structure of ∼ 300 km of the Mariana back‐arc spreading center south of the Pagan fracture zone at 17°33′N. Eight ridge segments, ranging from 14 to 64 km in length, are displaced as much as 2.7–14.5 km by both right‐ (predominantly) and left‐lateral offsets and transform faults. An axial ridge commonly occupies the middle portion of the rift valley and rises from 200 to 700 m above the adjacent sea floor, in places shoaling to a water depth of 3200 m. An exception is the 60‐km‐long segment between 16°58′ and 17°33′N where single peaks only a few tens of meters high punctuate the rift axis. Photographic evidence and rock samples reveal the presence of mostly pillow lavas outcropping on the axial ridges or peaks whereas the deeper parts of the rift valley floor (max. depth 4900 m) are heavily to totally sedimented. Abundant talus ramps along fault scarps testify to ongoing disruption of the crust. Lozenge‐shaped collapse structures are covered by layers of sediment up to tens of centimeters thick on the rift valley floor. The presence of discrete volcanic ridges in the southern Mariana back‐arc spreading region suggests that emplacement of oceanic crust at this slow spreading center occurs by `multi‐site' injection of magma. Along‐axis variations in length, crestal depth, and size of the axial ridges can be best explained by different stages in the cyclicity of magma supply along‐axis.

The Odra Flood event in a coupled physicalchemical-biological model (summary) - Thomas Neumann (Ocean Dynamics, 1998)

The exceptional Oder flood in summer 1997 — distribution patterns of the oder discharge in the Pomeranian Bight - Herbert Siegel; Wolfgang Matthäus; Regina Bruhn; Monika Gerth; Günther Nausch; Thomas Neumann; Christa Pohl (Ocean Dynamics, 1998)